High prevalence of celiac disease among Saudi children with type 1 diabetes: a prospective cross-sectional study - Al-Hussaini Abdulrahman; Sulaiman Nimer; Al-Zahrani Musa; Alenizi Ahmed; El Haj Imad (BMC Gastroenterology, 2012)
Abstract Background There is lack of data on prevalence of celiac disease (CD) in children with type 1 diabetes (T1D) in Arabs in the Middle East. The present investigation aims to study the prevalence rate and clinical characteristics of CD among Saudi children with T1D using a combination of the most sensitive and specific screening serologic tests (anti- tissue transglutaminase antibodies IgA [anti-TTG] and ednomyseal antibodies [EMA]) and to determine the lower cut-off value of anti- anti-TTG level that best predicts CD in children with T1D. Methods Children with T1D following in diabetic clinic have been prospectively screened for presence of CD, over a two-year period (2008–2010), by doing anti-TTG, EMA, and total IgA. Children with positive anti-TTG titres (>50 U/ml) and/or EMA and children with persistently low positive anti-TTG titres (two readings 20–50 U/ml; within 6 months intervals) had upper endoscopy and 6 duodenal biopsies. Results One hundred and six children with T1D have been screened for CD: age ranged between 8 months to 15.5 years (62 females). Nineteen children had positive anti-TTG and/or EMA, however only 12 children had biopsy proven CD (11.3%). Five of 12 had gastrointestinal symptoms (42%). Children with T1D and CD had significantly lower serum iron than children with T1D alone (8.5 μgm/L Vs 12.5 μgm/L; P = 0.014). The sensitivity and specificity of anti-TTG were 91.6% and 93.6%, with a positive and negative predictive value of 64.7% and 98.8%, respectively. Receiver operated characteristics analysis for the best cut-off value of anti-TTG level for diagnosis of CD was 63 units (sensitivity 100% and specificity 98.8%). Conclusion CD is highly prevalent among Saudi children with T1D. Anti-TTG titres more than 3 times the upper limit of normal has very high sensitivity and specificity for diagnosis of CD in T1D children.